ROS 2018
DOI: 10.20455/ros.2018.857
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in the Pathogenesis of Corneal Endothelial Dystrophies and Other Corneal Diseases

Abstract: | Cornea being constantly exposed to sunlight and atmospheric oxygen is readily prone to oxidative damages. The functional antioxidant signaling helps maintain the levels of reactive oxygen species in the cells and keeps the cornea healthy. Corneal endothelial dystrophies include a group of corneal diseases that are marked by progressive degeneration of corneal endothelium leading to loss of vision. The increased level of oxidative stress in several corneal endothelial dystrophies indicates that there might be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…On exposure to oxidative stress, the Keap1 structure changes, allowing Nrf2 to detach from Keap1 and translocate into the nucleus. After translocation into the nucleus, Nrf2 binds to ARE and enhances downstream antioxidant gene expression to maintain the redox balance in cells [ 17 ]. The Nrf2 nuclear translocation and ARE transactivation processes are regulated by multiple pathways including protein kinase C (PKC), phosphatidylinositol-3-kinase (PI3K)/protein kinase B (Akt)/GSK-3 β , p38 mitogen-activated protein kinase (MAPK), and nuclear factor kappa B (NF- κ B).…”
Section: Resultsmentioning
confidence: 99%
“…On exposure to oxidative stress, the Keap1 structure changes, allowing Nrf2 to detach from Keap1 and translocate into the nucleus. After translocation into the nucleus, Nrf2 binds to ARE and enhances downstream antioxidant gene expression to maintain the redox balance in cells [ 17 ]. The Nrf2 nuclear translocation and ARE transactivation processes are regulated by multiple pathways including protein kinase C (PKC), phosphatidylinositol-3-kinase (PI3K)/protein kinase B (Akt)/GSK-3 β , p38 mitogen-activated protein kinase (MAPK), and nuclear factor kappa B (NF- κ B).…”
Section: Resultsmentioning
confidence: 99%
“…In that case, the eye condition had been ongoing for more than 2 weeks, whereas clinical signs in the other two were only evident for 1-2 days. Previous papers have reported an increase in local oxidative damage (including MDA) in corneal tissue and aqueous humor from corneal diseases in humans [127][128][129], so this biomarker could be informative, as eye problems are common in captive elephants [6,130].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that vitamin D supplementation independently and significantly up‐regulates GCL and GR expression. As a result, there are increased levels of GSH in vitamin D‐treated cells and significantly lowered ROS levels in cells exposed to both control and high levels of glucose 94–96 . Studies on inflammation in adults and other chronic illnesses like tuberculosis found strong associations of vitamin D concentrations with higher GSH levels leading to the same conclusion that vitamin D up‐regulates GCL and GR to increase cellular glutathione formation 85 .…”
Section: Vitamin D and Its Effects On The Biosynthesis Of Cysteine And Glutathionementioning
confidence: 99%